Spring boot xue xi zhi nan : gou jian yun yuan sheng Java he Kotlin ying yong cheng xu = Spring boot : up and running - Heckler, Mark (O'Reilly jing pin tu shu xi lie., 2021)
Detailed summary in vernacular field.